1979
DOI: 10.1016/0378-1135(79)90047-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ambient temperatures on clinical and immune responses of pigs infected with transmissible gastro-enteritis virus

Abstract: Shimizu, M. and Shimizu, Y., 1979. Effects of ambient temperatures on clinical and immune responses of pigs infected with transmissible gastroenteritis virus. Vet. Microbiol., 4: 109--116.Two-to three-months-old pigs infected with transmissible gastroenteritis (TGE) virus showed no clinical response when housed at 30°C, but comparable infected pigs exposed to temperature changes from 30°C to 4°C following infection showed typical signs of TGE. Development of TGE-specific immune responses, as measured by blasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…The majority of herd outbreaks of PED occur during the colder months, especially between January and April (Tsuda, 1997). In TGE virus infection, (Shimizu et al, 1978;Shimizu and Shimizu, 1979) showed that a high ambient temperature resulted in increased disease resistance, while a low ambient temperature or temperature changes caused a dramatic enhancement in clinical signs. In the present study, 2±12-week old pigs were kept at 23± 248C throughout the study.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of herd outbreaks of PED occur during the colder months, especially between January and April (Tsuda, 1997). In TGE virus infection, (Shimizu et al, 1978;Shimizu and Shimizu, 1979) showed that a high ambient temperature resulted in increased disease resistance, while a low ambient temperature or temperature changes caused a dramatic enhancement in clinical signs. In the present study, 2±12-week old pigs were kept at 23± 248C throughout the study.…”
Section: Discussionmentioning
confidence: 99%
“…Cold per se lowers the new-born piglets resistance to micro-organisms resulting in increased incidence of infectious diseases such as transmissible gastro-enteritis (Shimizu, Shimizu and Kodama, 1978) and Escherichia coli enterotoxaemia (Armstrong and Cline, 1977). Cold per se lowers the new-born piglets resistance to micro-organisms resulting in increased incidence of infectious diseases such as transmissible gastro-enteritis (Shimizu, Shimizu and Kodama, 1978) and Escherichia coli enterotoxaemia (Armstrong and Cline, 1977).…”
Section: Climatic Effects Upon Productionmentioning
confidence: 99%
“…Analyzing blood for hormonal or immune status is useful for estimating states of metabolic disorders (Basset 1978) and infectious diseases (Shimizu and Shimizu 1979). However, the major prerequisite of using such methods is that the procedure itself must not be stressful to the animal.…”
mentioning
confidence: 99%